(untitled) (Heritage, 2020)
The subject of the research is the development of competencies for democratic culture in the digital age through the analysis of youth media culture. The aim of the research is that on the basis of the obtained results adequate solutions to the problem of media influence on the culture of communication and culture in general among young people can be proposed, and theoretically to determine how much the media influence the culture of communication and the development of youth awareness. young people. The paper concludes that the surveyed group of teenagers, 300 of them from Belgrade high schools, mostly watch television and follow an entertainment program, that the media in Serbia promote violence and hate speech, and that most of them enrich their language and culture of expression using electronic media, not a book. The results obtained confirm that the media, as they are today, have a very negative impact on the language culture and the culture of behavior of young people in general.